Experimental Determination of a Reflective Muffler Scattering Matrix for Single-Mode Excitation - Łukasz GORAZD (Archives of Acoustics, 2021)
The aim of the paper is to experimentally determine the scattering matrix S of an example reflective muffler of cylindrical geometry for Helmholtz number exceeding the plane wave propagation.